Features of civil legal status of religious organizations in Ukraine - Бутинський, Володимир Ярославович; Ніколова, М. М. (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2012)
In this article an authors examine the question of civil procedure for acquiring legal status of religious organizations  in  Ukraine.  Separately, explored problematic issues of  legal regulation of religious organizations.